Strategi Dalam Menangani Pembiayaan Bermasalah Pada Unit Syariah Bank Sumatera Utara - Nurul Inayah Siregar (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study aims to analyze the strategy in dealing with non-performing financing in the sharia unit of the Bank of North Sumatra. The research method used is qualitative analysis. The type of data used in this paper is qualitative data consisting of primary data and secondary data, among others, derived from research subjects and data from results that have been presented from an institution. From the results of the research conducted, the authors conclude that there are two strategies in dealing with problematic financing, namely by saving financing and completing financing. First, rescheduling financing, namely changes in the repayment schedule and credit period that obtain rescheduling facilities only debtors who meet certain requirements, including the debtor's business has the prospect of reviving and the debtor shows good faith. Second, Reconditioning (Requirements) is a change in part or all of the terms of financing which is not limited to changes in the payment schedule, time period and other requirements as long as it does not involve changes to the maximum balance of financing. Third, Restructuring, namely Changes in financing terms involving additional bank funds, conversion of all or part of interest arrears into principal participation in the company.